Saberes docentes dos instrumentistas professores: diálogo entre ensinar e avaliar num curso de performance em instrumento musical - Carvalho, Isamara Alves (2004)
The present research had as general objective knowing and discussing how professors of musical instruments, who teach children, report their teaching learning process according to two central axles: teaching and evaluating. In the first part we prioritize a theoretical explanation of the references and the methodology chosen for the development of this research. The first chapter presents some categories of teaching knowledgement starting with the references of TARDIF (2002) and MIZUKAMI (1996, 1999, 2001 and 2002), among others, show the authors who had endorsed our reflections on education and musical education focused in the teachlearning process and the democratization of the access, and on evaluation as learning aiding. We brought the concepts of diagnostic evaluation (LUCKESI, 1998)and armed loveliness (FREIRE, 1998, 1999, 2001a, 2001b and 2002, and LUCKESI, 1998). The second and last chapter of the first part describes the covered stages for the accomplishment of the present research. A qualitative research was chosen andwe carry through interviews in a half-structuralized characteristic, where ten professors of instrument had participated. Later, in the second part, we began the presentation and discussion (dialogue) of the results acquired in the interviews. It was possible to discuss different situations, dilemmas and reflections presented by the professors interviewed about the reality of the teach-learning process of the musical instrument lessons for children in a music school. The final dialogue shows some contributions of this research in the scope of the instrumentists teaching development and magnifying the academic production that focuses on the music schools professors.